2021
DOI: 10.1097/j.pain.0000000000002277
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of quantitative sensory testing-derived sensory phenotype to disease-modifying intervention in patients with entrapment neuropathy: a longitudinal study

Abstract: D.M Methods using N-(2propenyl) hexadecanamide and related amides to relieve pain. WO 2005/079771, Okuse K. et al Methods of treating pain by inhibition of vgf activity EP13702262.0/ WO2013 110945

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 84 publications
(139 reference statements)
0
36
1
Order By: Relevance
“…In the hand median nerve territories, including index finger, middle finger, and thenar area, the meta-analysis of 9 studies of 531 patients with CTS showed a significant loss of mechanical detection sensation in the CTS group (SMD, 1.04; 95% CI, 0.57, 1.52; P < 0.001), with considerable heterogeneity (I 2 = 87%; P < 0.001) 5,6,47,61,63,77,91,95,103 (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the hand median nerve territories, including index finger, middle finger, and thenar area, the meta-analysis of 9 studies of 531 patients with CTS showed a significant loss of mechanical detection sensation in the CTS group (SMD, 1.04; 95% CI, 0.57, 1.52; P < 0.001), with considerable heterogeneity (I 2 = 87%; P < 0.001) 5,6,47,61,63,77,91,95,103 (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis of 14 studies of CTS in the hand median nerve territories (index and middle fingers, carpal area, and thenar area) reported no difference in HPT (SMD, −0.22; 95% CI, −0.51, 0.06; P = 0.123), with substantial heterogeneity (I 2 = 81%; P < 0.001) 5,6,9,15,16,40,47,53,56,61,79,82,91,111 (Fig. 8A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations